Славянские мотивы в лирике тютчевской плеяды - Dmitrowski, Aleksiej (Acta Polono-Ruthenica, 2006)
Slavonic motives in lyric poetry of the late Russian romanticism - Tyutchev, A.K. Tolstoy, Polonsky, Fet, Maikov - are in the predominant importance of philosophical and historical as well as political views of Tyutchev. The development of these views from national and historical problems to the problems of ethos and novelist; and expansion of historical topics ranging from the Russian-Polish to the south-slavonic heritage. The development of genre from oratory monologue to the wide spectrum of lyrical and lyric-epic composition and up to folklore stylization.